Case report: Pediatric inflammatory multisystem syndrome temporally associated with SARS-CoV-2 with severe myocardial dysfunction. Is there any hope in immunotherapy? - Julita Tokarek; Emilian Budny; Renata Szmigielska (Kazimierz Wielki University, 2023)
Pediatric inflammatory multisystem syndrome temporally associated with SARS-CoV-2 (PIMS-TS) develops in a small percentage of children after COVID-19, however, it might cause severe myocardial dysfunction. The pathogenesis of this disease includes systemic hyper-inflammation with cytokine storm. This case report concerns a 12-year-old boy with PIMS-TS who presented severe respiratory and circulatory failure with increased inflammatory markers and significant reduction of left ventricle ejaculatory fraction (LVEF) from 65% to 35%. The recommended therapy with the use of vasopressors, corticosteroids, intravenous immunoglobulins and mechanical ventilation was introduced and his condition gradually improved. However, after few days, aggravation of cardiac symptoms occurred again and among other treatment, the therapy with the use of anakinra - the human interleukin 1 receptor antagonist protein was introduced. This case highlights a satisfactory regression of cardiac disturbances and generally favorable outcome of the treatment in patients with PIMS-TS with the use of immunomodulatory therapy.